Human Capital Investment under Asymmetric Information: The Pigovian Conjecture Revisited - Chang, Chun; Wang, Yijiang (Journal of Labor Economics, 1996)
This article investigates how human capital investment, labor turnover, and wages are jointly determined when the current employer knows more about a worker's productivity than potential employers. Results derived are quite different from, or unexplored by, the standard human capital theory. The authors show that the information asymmetry can cause an externality distortion in human capital investment because higher productivity due to the investment may not be recognized by the market. The investment level increases in the degree of firm specificity of human capital. The underinvestment problem is more severe when human capital is general than when it is firm-specific. Copyright 1996 by University of Chicago Press.